Biodiversity mediates top–down control in eelgrass ecosystems: a global comparative‐experimental approach - Duffy, J. Emmett; Reynolds, Pamela L; Boström, Christoffer; Coyer, James A; Cusson, Mathieu; Donadi, Serena; Douglass, James G; Eklöf, Johan S; Engelen, Aschwin H; Eriksson, Britas Klemens; Fredriksen, Stein; Gamfeldt, Lars; et al. (Ecology letters, 2015)
Nutrient pollution and reduced grazing each can stimulate algal blooms as shown by numerous experiments. But because experiments rarely incorporate natural variation in environmental factors and biodiversity, conditions determining the relative strength of bottom–up and top–down forcing remain unresolved. We factorially added nutrients and reduced grazing at 15 sites across the range of the marine foundation species eelgrass (Zostera marina) to quantify how top–down and bottom–up control interact with natural gradients in biodiversity and environmental forcing. Experiments confirmed modest top–down control of algae, whereas fertilisation had no general effect. Unexpectedly, grazer and algal biomass were better predicted by cross‐site variation in grazer and eelgrass diversity than by global environmental gradients. Moreover, these large‐scale patterns corresponded strikingly with prior small‐scale experiments. Our results link global and local evidence that biodiversity and top–down control strongly influence functioning of threatened seagrass ecosystems, and suggest that biodiversity is comparably important to global change stressors.